Privacy levels for computer forensics: toward a more efficient privacy-preserving investigation - Halboob, Waleed Abduljabbar Mohammed; Mahmod, Ramlan; Udzir, Nur Izura; Abdullah @ Selimun, Mohd Taufik (Elsevier, 2015)
Computer forensics and privacy protection fields are two conflicting directions in computer security. In the other words, computer forensics tools try to discover and extract digital evidences related to a specific crime, while privacy protection techniques aim at protecting the data owner’s privacy. As a result, finding a balance between these two fields is a serious challenge. Existing privacypreserving computer forensics solutions consider all data owner’s data as private and, as a result, they collect and encrypt the entire data. This increases the investigation cost in terms of time and resources. So, there is a need for having privacy levels for computer forensics so that only relevant data are collected and then only private relevant data are encrypted. This research paper proposes privacy levels for computer forensics. It starts with classifying forensic data, and analyzing all data access possibilities in computer forensics. Then, it defines several privacy levels based on the found access possibilities. The defined privacy levels lead to more efficient privacy-preserving computer forensics solution.